2013
DOI: 10.3390/ijms141121819
|View full text |Cite
|
Sign up to set email alerts
|

Opposite Associations of Plasma Homoarginine and Ornithine with Arginine in Healthy Children and Adolescents

Abstract: Homoarginine, a non-proteinogenic amino acid, is formed when lysine replaces ornithine in reactions catalyzed by hepatic urea cycle enzymes or lysine substitutes for glycine as a substrate of renal arginine:glycine amidinotransferase. Decreased circulating homoarginine and elevated ornithine, a downstream product of arginase, predict adverse cardiovascular outcome. Our aim was to investigate correlates of plasma homoarginine and ornithine and their relations with carotid vascular structure in 40 healthy childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 57 publications
(93 reference statements)
1
6
0
Order By: Relevance
“…The second interesting finding of the present study is that the plasma concentrations of hArg and ADMA did not correlate with each other in RA. However, in our RA patients circulating hArg and ADMA correlated with the plasma concentration of Arg, i.e., their common precursor, confirming data reported by other groups for healthy and ill subjects (Jaźwińska-Kozuba et al 2013;Khalil et al 2013;van der Zwan et al 2013). In PAOD and CAD, plasma thCys and ADMA also did not correlate with each other.…”
Section: Discussionsupporting
confidence: 93%
“…The second interesting finding of the present study is that the plasma concentrations of hArg and ADMA did not correlate with each other in RA. However, in our RA patients circulating hArg and ADMA correlated with the plasma concentration of Arg, i.e., their common precursor, confirming data reported by other groups for healthy and ill subjects (Jaźwińska-Kozuba et al 2013;Khalil et al 2013;van der Zwan et al 2013). In PAOD and CAD, plasma thCys and ADMA also did not correlate with each other.…”
Section: Discussionsupporting
confidence: 93%
“…Specifically, one study reported a significant correlation between ADMA concentration and cIMT in Australian children [ 35 ]. However, this association was not significant for a study conducted in Polish children [ 36 ]. Therefore, whether circulating ADMA levels are a biomarker for atherosclerosis may be dependent upon the geographical location and ethnicity of the population of interest.…”
Section: Discussionmentioning
confidence: 87%
“…Interestingly, in another study with 40 healthy children and adolescents, the same median plasma homoarginine concentration was measured as in our controls. An association between intimamedia thickness or extramedial thickness of common carotid arteries and homoarginine could not be found (22). In general, children with T1D however are at high risk of premature, subclinical atherosclerosis which has been confirmed by providing evidence of endothelial dysfunction and increased intimamedia thickness (7,23).…”
Section: Discussionmentioning
confidence: 96%